Perichromosomal protein Ki67 supports mitotic chromosome architecture. (9th September 2016) - Takagi, Masatoshi; Natsume, Toyoaki; Kanemaki, Masato T.; Imamoto, Naoko
Abstract : Although the condensin complexes and topoisomerase IIα (TopoIIα) are the central players in mitotic chromosome formation, they are insufficient for its completion, and additional factors involved in the process have been extensively sought. In this study, we examined the possibility that Ki67, a perichromosomal protein widely used as a cell proliferation marker, is one such factor. Using a combination of auxin‐inducible degron and CRISPR–Cas9‐based gene editing technologies, we generated a human HCT116 cell line in which Ki67 is rapidly depleted in a few hours. The removal of Ki67 before mitotic entry did not impact the early mitotic chromosome assembly observed in prophase but subsequently resulted in the formation of misshapen mitotic chromosomes. When Ki67 was removed after mitotic entry, preassembled rod‐shaped mitotic chromosomes became disorganized. In addition, we show that Ki67 and TopoIIα are reciprocally coimmunoprecipitated from mitotic cell extracts. These observations indicate that Ki67 aids the finalization of mitotic chromosome formation and helps maintain rod‐shaped chromosome architecture, likely in collaboration with TopoIIα. Together, these findings represent a new model in which mitotic chromosome architecture is supported both internally and externally. Abstract : We revealed that Ki67, a perichromosomal protein, has a role in the assembly and the maintenance of mitotic chromosome architecture, likely in collaboration with TopoIIα. We represented a new model in which mitotic chromosome architecture is supported both internally and externally.